OPTIMALISASI HASIL INVESTASI LEMBAGA KEUANGAN SYARIAH (STUDI KASUS PADA INSTITUSI ASURANSI SYARIAH) - ., Isfandayani (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2011)
The aim of this thesis is to analyze the investment strategy of PT Asuransi Takaful Keluarga in allocating fund on several investment instruments in order to obtain an optimum return. As we all know, invesment is one of the most important factors in fund management by a life insurance company. This is especially for Islamic insurance company which from the beginning has programmed a product with saving and non saving system, with outcome sharing for its customers. A company must manage its fund optimally to obtain a maximum return. However syariah funding company to be consistent in investing to avaid investmentgets containing maysir, gharar, and riba. In addition, there are also limitations of investment portions from the Indonesi ministry of Finane for syariah company. In this thesis, the author limits her analysis on five investment instrument, are deposits, shares, mutual fund, obligations, and murabahah financing. Those analysis also include kekafahan in kesyariahan each instrument, whether it is investment types in general or diversification outcome to any institution. However the observation was carried out only to observe investment in 2003. The processing of data was done by gathering investment data of five instrument, calculating outcome sharing or the obtained return this was followed by comparing the maximum outcome from another strategy through Lindo Program by changing the portion of each instrument and of course, according to the valid positive law. The outcome shares that a gifater return was obtained by an investment allocation strategy different from the policy of PT Asuransi Takaful Keluarga. Due to such fact it is haped that this method could be applied in composing an investment strategy for syariah companies particularity PT Asuransi Takaful Keluarga